Pengaruh Terapi Akupresur Terhadap Mual Muntah Lambat Akibat Kemoterapi pada Anak Usia Sekolah yang Menderita Kanker di RS Kanker Dharmais Jakarta - Siti Rukayah; Fitria Prihatini; Evi Vestabilivy (STIKes Persada Husada Indonesia, 2014)
Acupressure is one of the complementary therapy on children who experience delayed chemotherapy-induced nausea and vomiting (CINV). Nausea vomiting is a side effect that could cause stress toward children and their family. The purpose of this research was to identify the effect of acupressure to delayed chemotherapy-induced nausea and vomiting in school age children who suffered from cancer at Kanker Dharmais Hospital Jakarta. The study design was quasi eksperiment with pre-post test without control design from of acupressure point P6 and St36 2 times for 3 minutes every 6 hours. Taking sample by using the methode of consecutive sampling, 20 respondents of school-aged children were chosen for the study. The result of the study showed that there is a significant decreases of the mean delayed nausea and vomiting scores after acupressure. The conclusion of this study is that the acupressure can decrease the delay CINV in school age children that are suffering from cancer. The recommendations from the acupressure research can be applied as a non-pharmacological therapy to reduce nausea and vomiting caused by chemotherapy than in children.